MiR-214 increases the sensitivity of breast cancer cells to tamoxifen and fulvestrant through inhibition of autophagy. Issue 1 (December 2015) - Yu, Xinfeng; Luo, Aiping; Liu, Yicong; Wang, Shuqing; Li, Ye; Shi, Wenna; Liu, Zhihua; Qu, Xianjun
Abstract Background Tamoxifen (TAM) and fulvestrant (FUL) are the major drugs for patients with estrogen receptor-positive (ER+ ) breast cancers. However, the development of endocrine resistance is the impediment for successful treatment. We aimed to explore the mechanisms of endocrine resistance and therapeutic strategy for overcoming resistance against TAM and FUL. Methods Experiments were performed in ER+ and estrogen/TAM-sensitive MCF7 cells and antiestrogen-resistant MCF7/LCC9 cells. The expression of miR-214 and uncoupling protein 2 (UCP2) was determined by RT-qPCR and Western blot in breast cancer cells and human breast cancer tissue specimens. Cell autophagy was examined by fluorescent probe monodansyl cadaverine (MDC) and GFP-LC3-II-positive punctate identified by confocal microscopy. Apoptotic cells were determined by Annexin V-FITC/PI staining. The potential regulatory target of miR-214 was determined by prediction tool, target protein expression and luciferase reporter assay. Results 4-OHT/FUL treatment resulted in induction of apoptosis as well as autophagy in breast cancer cells. Autophagy might be the major cause of endocrine resistance to 4-OHT or FUL. MiR-214 increased the sensitivity of breast cancer cells to the 4-OHT/FUL-induced apoptosis through inhibition of autophagy. Importantly, a negative correlation was established between miR-214 and UCP2 in human breast cancer tissue specimens assayed by RT-qPCR. UCP2 was identified to be a direct target of miR-214. Further study in MCF7/LCC9 cells indicated that endocrine resistance might arise from activation of the PI3K-Akt-mTOR pathway, thereby inducing autophagy by overexpression of UCP2. Conclusion MiR-214 increased the sensitivity of breast cancer cells to TAM and FUL through inhibition of autophagy by targeting UCP2. MiR-214 shows potential as a novel therapeutic strategy for overcoming endocrine resistance in ER+ breast cancers.